Surgical Excision in the Management of Rhinophyma: A Case Report - Adina Miltania Tasmil; Riana Miranda Sinaga (Indonesian Journal of Global Health Research, 2025)
Rhinophyma is the most severe and disfiguring manifestation of phymatous rosacea, characterized by progressive hypertrophy of sebaceous glands and connective tissue on the nasal skin. It often leads to both aesthetic and functional impairment. Various treatment options are available, with surgical excision considered the most definitive for advanced cases. This case report aims to highlight the clinical presentation, diagnostic approach, and the effectiveness of surgical excision combined with electrocautery as a treatment modality for rhinophyma. We report a case of a 49-year-old male presenting with progressive nasal enlargement, nodularity with sharply demarcated borders, an irregular surface, and a firm, slightly compressible consistency. Clinical and histopathological examination confirmed the diagnosis of rhinophyma. The patient underwent surgical excision followed by electrocauterization. The procedure was well-tolerated without intraoperative or postoperative complications. Follow-up showed satisfactory cosmetic improvement and no signs of recurrence. The management of rhinophyma varies depending on disease severity. In advanced cases, surgical excision remains the treatment of choice. It provides immediate debulking of hypertrophic tissue and restoration of nasal contour. Combined with electrosurgical techniques, this method offers good cosmetic and functional outcomes, minimal scarring, and a low recurrence rate. It addresses both functional obstruction and cosmetic disfigurement, contributing to improved quality of life.